Simulasi Penggunaan Program Geostudio Slope/W 2007 dalam Menganalisis Stabilitas Lereng Dengan Jenis Tanah Lempung Berpasir pada Kondisi Tidak Jenuh, Kondisi Jenuh Sebagian, dan Kondisi Jenuh - pentawan, yota; Afriani, Lusmeilia; Siregar, Amril Ma'ruf (Universitas Lampung, 2017)
Landslide is a natural disaster that often occurs in Lampung Province, particularly in WestLampung regency. The sliding occurs due to an increase in soil pore water stress in the rainyseason. Based on the research on the slopes, there is a safety factor value that can be used as areference for the degree of slope stability. One method to analyze the value of slope safety factoris by using the Geostudio Slope / W 2007 program.In this study, some cross sections of slope were simulated with 4 different water table conditions.The required soil properties index are: cohesion, c; natural angle of repose, φ; and unit weight ofdensity, γ .The analysis result shows that slope transversal cut shape have influence on slope stability. Theanalysis results on slopes with saturated conditions have a safety factor value of <1.25 and areclassified on unsafe slopes. In the unsaturated condition the whole simulation is classified as astable slope with a safety factor value> 1.25. Based on the analysis result, it can be inferred thatthe slope has insecured status. Thus, it is suggested to conduct such actions in order to preventlandslide.Key words : soil, slope stability, safety factor, geostudio slope/w.